Penerapan Layanan Bimbingan Kelompok Dengan Metode Relaksasi Untuk Mengatasi Kecemasan Lansia - Nofria Rahmadani; Kusnadi Kusnadi; Lena Marianti (Journal of Society Counseling, 2023)
Old age brings physical, psychological, and bodily changes. The decline in physical strength occurs during the elderly phase, causing difficulties and anxiety. Group counseling services with a relaxation method help the elderly overcome anxiety and achieve a happy elderly phase. Therefore, a research titled "Implementation of Group Counseling Services with Relaxation Method for Addressing Elderly Anxiety at Harapan Kita Social Welfare Home in Palembang" was conducted. The research aims to understand the behavior of the elderly and analyze the implementation of group counseling services for addressing elderly anxiety at Harapan Kita. Qualitative approach with field research methodology was used, employing observation, interviews, and documentation for data collection. Findings indicate varied behavior influenced by motivation, health, social support, and individual preferences. Implementing group counseling with relaxation method shows positive potential in alleviating elderly anxiety. The program consists of initial, transitional, working, and concluding stages, helping the elderly understand and apply relaxation techniques such as muscle relaxation and recitation. These methods enable focus and calmness, reducing anxiety symptoms like restlessness, tension, fear, and nervousness. Group counseling provides support and fosters experience sharing, an effective strategy for enhancing elderly well-being at Harapan Kita Social Welfare Home in Palembang.